白芍藥 추출물의 전립선 암세포 고사 유도 효과 및 기전 연구 - 권강범(Kang Beom Kwon); 김은경(Eun Kyung Kim); 김경종(Koyung Jong Kim); 강길성(Gil Seong Kang); 김영선(Young Sun Kim); 김인규(In Kyu Kim); 김인섭(In Seob Kim); 김인수(In Soo Kim); 이수경(Su Kyung Lee); 서은아(Eun A Seo); 류도곤(Do Gon Ryu) (동의생리병리학회지, 2004)
The aim of this study was to investigate the apoptotic effect and its mechanism on Radix Paeoniae Alba Extract(RPAE) in DU145 human prostate cancer cell line. RPAE induced apoptosis in a dose-dependent manner in DU145 cells as confirmed by both discontinuous DNA fragmentation using Hoechst33342 staining and poly-(ADP-ribose) polymerase(PARP) cleavage, which are apoptotic signs. To clarify the mechanisms on RPAE-induced apoptosis, we examined the p50(NF-κB subunit), IκBα, PTEN and Par-4 protein expression using Western blotting. Treatment with RPAE resulted in the decrease of p50 expression by IκBα increase, which resulted in Par-4 increase and bcl-2 decrease in DU145 cells. These results suggest that apoptosis of DU145 cells by RPAE involved decreases of NF-κB activation and bcl-2 expression, increase of Par-4 protein expression. KCI Citation Count: 2